A new species of the genus Xysticus C. L. Koch from Turkey (Araneae: Thomisidae) - Demi̇r, Hakan; Topçu, Aydin; Türkeş, Tuncay (Zootaxa, 2006)
A new species of Xysticus C. L. Koch, 1835 is described from Turkey. Differences between the new species and related species are discussed.